Review of Nikos Potamianos, “Της αναιδείας θεάματα”: Κοινωνική ιστορία της Αποκριάς στην Αθήνα, 1800–1940 : [Spectacles of insolence: The social history of carnival in Athens, 1800–1940] - Sergidou, Katerina (Historein, 2023)
Review of Nikos Potamianos, “Της αναιδείας θεάματα”: Κοινωνική ιστορία της Αποκριάς στην Αθήνα, 1800–1940 [Spectacles of insolence: The social history of carnival in Athens, 1800–1940]. Iraklio: Crete University Press, 2020. 310 pp.